Integrating genetic counseling and testing in the pediatric oncology setting: Parental attitudes and influencing factors. Issue 10 (11th July 2019) - Desrosiers, Lauren R.; Quinn, Emily; Cramer, Stuart; Dobek, Whitney
Abstract: Background: Cancer predisposition syndromes (CPS) are caused by germline pathogenic variants that put an individual at increased risk of developing cancer throughout their lifetime. It is estimated that approximately 10‐15% of children with cancer have an underlying CPS. Although research has investigated the clinical utility of genetic testing for children diagnosed with cancer, this study aimed to gain a deeper understanding of parental attitudes toward genetic testing in this population. Procedure: Attitudes toward genetic counseling and testing among parents of children diagnosed with cancer were solicited through questionnaires distributed to a pediatric cancer clinic and online support groups. Quantitative data were analyzed using descriptive statistics and chi‐square tests for association. Results: The majority of participants had prior knowledge of genetic counseling (64.3%), yet most were not offered genetic counseling (59.5%). Fifty percent of parents reported interest in pursuing genetic counseling/testing and 31.0% reported uncertainty. Statistically significant associations were identified between interest in genetic counseling/testing and the child's age at diagnosis, child's sex, and participant annual income ( P  < .05). Conclusions: Parents of children diagnosed with cancer generally expressed interest in genetic counseling/testing; however, notable uncertainty was also reported. In light of this uncertainty, genetic counselors have an ideal skill set to engage families in their decision‐making process as they weigh the benefits and drawbacks to pursuing genetic testing among this population. Demonstrated parental receptiveness to genomic technologies supports expansion of genetics providers in pediatric oncology care.